Digital contact tracing in epidemics: fast tracking the future - Khader, Khalid; Chintha, Sujatha (International Journal Of Community Medicine And Public Health, 2022)
The COVID pandemic has brought unprecedented changes in the current healthcare model, more as a necessity than by choice. The rapid unraveling of the pandemic has fast tracked the use of technology and artificial intelligence in healthcare systems by identifying and implementing more efficient processes to mitigate the crisis. Digital contact tracing technology (DCTT) has been hailed as the savior for opening up the community towards some semblance to the previous normal. Understanding contact tracing as both a proactive tool in the containing of an epidemics and as a reactive tool in limiting damages after spread is of utmost importance before taking a call into its effectiveness and implication on privacy of the individuals involved. The current pandemic response is like building a plane during its flight, and hence the risks involved in understanding the disease and mitigating the problems due to the novel nature of the disease needs to be done in real time. The political and social outcries on the use of DCTT are enough reasons for caution in applying previously unperfected technologies in diseases whose natural course has not yet been fully understood. The relationship between epidemics and contact tracing, conventional contact tracing, DCTT, different models of DCTT used during the current epidemic, limitations of DCTT and the future of incorporating DCTT into healthcare systems from the view of epidemiology and patient safety will be the primary focus of this article.